Effectiveness of an Instructional Program Concerning Non-Pharmacological Guideline on Controlling Essential Hypertension among Patients at AL-Sader Hospital in AL-Najaf AL-Ashraf City - Abdul-hussain, Mustafa; hassan, huda (Iraqi National Journal of Nursing Specialties, 2020)
Objective: The aims of present study to detect the effectiveness of instruction program of non-pharmacological guideline on blood pressure and laboratory test. Methodology: A pre-experimental study was conducted in Al-Sader Teaching Hospital from 8th of September 2019 to 25th of May 2020, in order to find out the effectiveness of instruction program concerning non-pharmacological guideline on controlling essential hypertension among patients. A non- probability (purposive sample) of 50 patients with essential hypertension is selected. Those patients are already diagnosed with Essential Hypertension and had already used the medication and they visited the hospitals for treatment or follow-up or both. A questionnaire is constructed to assess the effectiveness of the instruction program for controlling essential hypertension which consist of four part Part one: It is concerned with the patients’ socio-demographic data which include (gender, age, level of education, marital status, economic status, and occupation) Part two: Consist of patient health behavior which as exercise, weight, height and assessing of BP. Part three: included list of Laboratory test Part four: deals two domain related to patient’s knowledge about hypertension which as 15 items and Second domain related to DASH regimen which as 13 items. The validity of the questionnaire and the instructional program had been achieved by 10 panel of experts, the descriptive and inferential statistics was used to data analysis of the results. Results: The results of the study indicated that the stage of hypertension according to category of hypertension was 44% stage 3 the pre-test and their hypertension was improved in the post-test where become 26% prehypertension, and 22% norm tension. Recommendations: The study recommended that the instructional guideline (DASH) should be used and applied to all patients’ to health institutions with essential hypertension by the Ministry of Health and health care centers.